Double‐blind placebo‐controlled trial of the effect of omalizumab on basophils in chronic urticaria patients. Issue 2 (12th December 2017) - Jörg, L.; Pecaric‐Petkovic, T.; Reichenbach, S.; Coslovsky, M.; Stalder, O.; Pichler, W.; Hausmann, O.
Summary: Background: Omalizumab has been shown to be effective in treating chronic spontaneous urticaria (CSU). The reduction in FcεRI receptor density on the surface of basophils and mast cells is thought to play a major role in its effectiveness. We conducted a double‐blind, randomized, placebo‐controlled trial to investigate the mode of action of omalizumab in patients with antihistamine‐resistant CSU. Methods: Thirty patients were randomized in a 2:1 ratio to receive either 300 mg omalizumab or placebo. Four monthly applications of omalizumab/placebo were followed up with a visit 2 months after the last injection. The primary endpoint was the FcεRI receptor density change on basophils. Results: Omalizumab led to a significant reduction in FcεRI receptor density on basophils as soon as 1 week after the first injection: baseline omalizumab vs placebo group, 80.31 ± 47.18 × 10³ vs 78.29 ± 45.09 × 10³ receptors/basophil ± SD; 1 week, 72.89 ± 47.79 × 10³ vs 27.83 ± 20.87 × 10³, P  = .001. This effect continued during the treatment phase and persisted for 2 months after the last injection: 93.81 ± 56.50 × 10³ vs 21.09 ± 15.23 × 10³, P  = .002. Values for basophil "releasability" and the basophil activation test (CU‐BAT) of patient serum using donor basophils were unchanged despite treatment: CU‐BAT, CD63 10.75% (7.35) in the placebo group vs 8.35% (15.20) in the omalizumab group, P  = .778. Conclusion: We demonstrated a rapid reduction of FcεRI receptor density on basophils following treatment with omalizumab. Because CU‐BAT using well‐characterized, omalizumab‐naïve donor basophils did not change during the treatment phase, autoreactive serum factors seem to remain unaltered. This points towards a cellular effect of omalizumab on basophils. To predict the omalizumab response time and to monitor disease, FcεRI density and CU‐BAT might be promising cellular‐based assays.